(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The present article is a revisit of the doctoral research where I researched the games of Máscara in Candomblé in order to produce strategies of physical compositions for the contemporary scene. From the perspective of Encruzilhada, I crossed the perception of these Mask games with the methodology of Jacques Lecoq and other directors of the Western Theater. Based on a methodological triad that encompasses bibliographical research, field research and scenic laboratory, this article presents some of the strategies that were developed during the doctorate.